Gametophyte development in Cheilanthes Viridis Var. Glauca (adiantaceae) with special reference to Apogamy - Anderson, Cindy Louise (My University, 1992)
The gametophyte generation of the fern life cycle is initiated with the formation of spores. The spores of C. viridis (Fonsic) Swarts var. glaeca (Sim) schelp Anthony are trilete and have a cristate spore wall ornamentation. Under favourable conditions the spores of C. viridis var. glauca show polar germination [Abbreviated Abstract. Open document to view full version]
A dissertation submitted to the faculty of science university of the Witwatersrand, Johannesburg for the Degree of Master of Science Johannesburg 1992
Keywords: Adiantaceae; Cheilanthus; Fern gametophytes; Apogamy; Plants--Reproduction